Économie de l’échange dans les sciences-fictions étasuniennes et soviétiques - Vignon, Daphné; Gilbert, Jacques Athanase (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Comparing the treatment of the cybernetic motif in U.S. and Soviet science fiction allows us to question two ways of apprehending the modalities of exchange. Beyond ideological dissensions, the aim is to examine the way in which probabilities are mobilized to define not only the complexity, but also the final purpose of statistical “prediction”. Indeed if statistical “prediction” is exercised without restraint, it empties the exchange of words, including its deliberative dimension.